Penguatan Kapasitas UMKM Perikanan melalui Teknologi Bioflok dan Pemijahan Semi-Alami: Studi Desa Binaan Universitas Riau di Pekanbaru - Indra Lesmana; Ando Fahda Aulia; Desi Rahmadani Siagian; Midawita Misdawita; Rodi Firmansyah; Ade Yulindra (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2025)
Aquaculture-based micro, small, and medium enterprises (MSMEs) often struggle with limited technology, weak management, and high production costs. This program aimed to strengthen the capacity of aquaculture MSMEs through the application of biofloc technology and semi-natural spawning techniques in catfish culture. The intervention was carried out with the “Maju Bersama” Community Business Group (KUBE) in Industritenayan, Pekanbaru, under the Community Development Program (Desa Binaan) of Universitas Riau. Methods included counseling, training, workshops, demonstrations, and mentoring on hatchery techniques, grow-out management, and entrepreneurship. Program evaluation was conducted using a participatory approach, measuring improvements in skills, seed production, and system sustainability. Results showed increased knowledge and skills of the target group in catfish breeding and farming. The establishment of a hatchery unit enabled independent seed production, reducing dependence on external suppliers and lowering costs. Biofloc systems improved feed efficiency, water quality, and survival rates. These outcomes demonstrate that integrating aquaculture technology with business capacity building can be an effective model of community empowerment. The program contributed to income generation, MSME independence, and supported Sustainable Development Goals (SDGs) related to decent work and economic growth.